FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI ETIS PENGGELAPAN PAJAK - Zainuddin Zainuddin; Suriana Ar Mahdi; Amelia Abriani Ismail (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
This study aims to determine and analyze the influence of machiavellian, love of money, tax systems, tax rates, tax audits, tax discrimination, technology and tax information on ethical perceptions of tax evasion. The population in this study were all corporate taxpayers registered at KPP Pratama Ternate. The research sample was randomly selected using random sampling method. The number of samples is 347 corporate taxpayers who are registered at KPP Pratama Ternate. This survey research instrument using a questionnaire. Data were analyzed by Smart-PLS. The results of hypothesis testing concluded that: love of money and tax discrimination have a positive effect on tax evasion ethics, while machiavellian, tax systems, tax rates, tax audits, and taxation technology and information have no effect on tax evasion ethics.